TANGGUNG JAWAB TERBATAS DAN KEPASTIAN HUKUM PERSEROAN PEROARANGAN TERHADAP PEROLEHAN KREDIT PERBANKAN - Ambon, Is Faisal; Franciska, Wira; Atmadja, Dhody.AR.Widjaja (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The government aims to support the development of the economy in Indonesia by creating a new business entity in the form of a legal entity, namely a Sole Proprietorship, which is regulated in Law Number 6 of 2023 in lieu of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation, which aims to make it easier for the public to form businesses for Micro and Small Enterprises (MSEs) and can have the same legality and legal certainty as Limited Liability Companies in general as a business entity with legal status. Limited liability of shareholders or founders of a sole proprietorship with MSE criteria is limited to the paid-up capital and is absolutely applicable. Shareholders of the Company for MSEs do not have personal responsibility for the obligations made by the Company and are not responsible for losses exceeding the shares owned, with all activities carried out by the Individual Company in this MSE so that they can easily obtain additional credit capital with a large financing value to run their business by having to fulfill several aspects as an assessment by the Bank as a creditor. The type of research used in this study is normative juridical with a statutory, conceptual, and interview approach from several informants from the Bank. The source of legal materials in this study is secondary data consisting of primary, secondary, and tertiary legal materials using legal material collection techniques, namely literature studies. The results of this study are firstly the characteristics of limited liability of a Sole Proprietorship, the criteria for MSEs are limited to the paid-up capital, which is absolutely applicable, and is not responsible for losses exceeding the shares owned, and secondly the legal certainty of a sole proprietorship in obtaining banking credit facilities as a debtor to increase its business without leaving the prudential aspects owned by the Bank so that the Bank can adjust the provision of credit by adjusting to existing regulations.